Perbandingan Harga Saham Perusahaan Restoran Makanan Cepat Saji di BEI Sebelum dan Sesudah Gencatan Senjata Palestina-Israel 19 Januari 2025 - Muthia Rahma Putri Dahlia; Nizwan Zukhri; Willa Fatika Sari (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
This study aims to examine the differences in stock prices before and after the Palestine-Israel ceasefire event in fast-food restaurant companies,  Pizza Hut and KFC. International-scale events may influence investor perceptions, as reflected in stock price movements in the capital market. This study employs a comparative quantitative approach using stock price data collected over 30 days before and 30 days after the ceasefire event. The analyzed data consist of secondary data processed through descriptive statistics, normality tests, and hypothesis testing. The findings indicate that the average stock price of PZZA increased after the event, whereas FAST experienced a decline in its average stock price. These results reveal differences in stock prices between the periods before and after the ceasefire event in both companies. The findings further suggest that geopolitical events are associated with changes in stock prices in the fast-food restaurant industry, although market responses differ across companies. Therefore, future studies are recommended to expand the scope of research objects and extend the observation period to obtain a more comprehensive understanding of market responses to international events.